Religious Conversion to Converts at the Indonesian Chinese Islamic Association Palembang, Indonesia - Fadhilatunnisa Fadhilatunnisa; Iredho Fani Reza; Zaharuddin Zaharuddin (‎‎‎TAZKIYA Journal of Psychology, 2022)
The ethnic Chinese in Indonesia mostly adheres to the religion of their ancestors, such as Christianity, Confucianism, and Buddhism. Only a small portion of the ethnic Chinese converted to Islam, and when they embraced Islam became a minority the Chinese community. Those who are a minority among minorities, are very important to research. This study aims to determine the experience of religious conversion in converts at the Indonesian Chinese Islamic Association (Persatuan Islam Tionghoa Indonesia, PITI) of Palembang. This research uses a qualitative method with a descriptive approach. The participants of this study were three Chinese converts. The data of this study were obtained by semi-structured interviews. Then the results were analyzed using the Miles and Huberman method. The results of this study indicate there are four main problems experienced by participants, namely towards the process of religious conversion, when converting to religion, after becoming a convert, and changing themselves. In general, this research concludes that participants experience changes that occur not only in themselves, but also in their social interactions.